Exploring the Sociodemographic and Behavioral Status of People Living with Hypercholesterolemia in Saudi Arabia: A Nation-Wide Cross-Sectional Study - Almubark SA; Almubark RA; Althumiri NA; Alhamdan AAH; AlNujaidi HY; Alzayer R; Alkhamaali Z; BinDhim NF (Dove Medical Press, 2023)
Sarh A Almubark,1 Rasha A Almubark,2 Nora A Althumiri,2 Adel AH Alhamdan,3 Heba Y AlNujaidi,4 Reem Alzayer,5 Zaied Alkhamaali,6 Nasser F BinDhim2,7,8 1Health Services Management Department, Faculty of Public Health, Umm Al-Qura University, Makkah, Kingdom of Saudi Arabia; 2Scientific Department, Sharik Association for Health, Riyadh, Kingdom of Saudi Arabia; 3Community Health Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, Kingdom of Saudi Arabia; 4College of Public Health, Imam Abdulrahman Bin Faisal University, Dammam, Kingdom of Saudi Arabia; 5Pharmacy Department, Mohammed Al-Mana College for Medical Sciences, Dammam, Kingdom of Saudi Arabia; 6Medical Devices Department, Saudi Food and Drug Authority, Riyadh, Kingdom of Saudi Arabia; 7College of Medicine, Alfaisal University, Riyadh, Kingdom of Saudi Arabia; 8Decision Support for Research and Studies, IDM, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Sarh A Almubark, Umm Al-Qura University, Al Awali Street, Makkah, 21955, Kingdom of Saudi Arabia, Tel +966544945596, Email semubarak@uqu.edu.saIntroduction: Hypercholesterolemia (HC) is a well-known risk factor for cardiovascular diseases, which are the leading cause of death worldwide. Many factors can contribute to HC, including advanced age, chronic diseases (such as diabetes and nephrotic syndrome), and the use of certain medications.Aim: Our goal was to compare the sociodemographic, behavioral, and other comorbid conditions of adult participants living with HC in Saudi Arabia to the general population.Methods: This is a secondary data analysis from the Sharik Health Indicators Surveillance System (SHISS). SHISS consists of cross-sectional phone interviews conducted in all administrative regions of Saudi Arabia on a quarterly basis. Participant recruitment was limited to Arabic-speaking Saudi residents who were ≥ 18 years old.Results: Out of 20,492 potential participants contacted in 2021, 14,007 completed the interview. Of the total participants, 50.1% were male. The mean age of participants was 36.7 years, with 1673 (11.94%) having HC. A regression model showed that participants with HC had a higher likelihood of being older, living in Tabouk, Riyadh, or Asir regions, being overweight or obese, having diabetes, hypertension, genetic or heart diseases, or having a higher risk of depression. Gender, all types of smoking, physical activity, and education level were eliminated from the model.Discussion: In this study, participants with HC were identified with some co-existing conditions that may affect the progression of the disease and the participants' quality of life. This information could assist care providers in identifying patients who are at higher risk, improve screening efficiency, and improve disease progression and quality of life.Keywords: cardiovascular diseases, hypercholesterolemia, Saudi Arabia, chronic disease, epidemiology